WTO Principles in the Jurisprudence of International Commercial Arbitration: A Comparative Institutional Study of Great Britain and Russia - INSHAKOVA, Agnessa; FROLOV, Daniil; KAZACHENOK, Svetlana; MARUSCHAK, Irina (Journal of Advanced Research in Law and Economics; Vol 7 No 3 (2016): JARLE, Volume VII, Issue 3(17), Summer 2016, 2016)
The paper is devoted to the research of the impact of Russia’s accession to the WTO of the legal institutions in Russia. The major legal body in Russia that is involved in trade dispute settlement is the International Commercial Arbitration Court at the Chamber of Commerce and Industry of the Russian Federation that following the country’s accession to the WTO faces the challenge to comply with the WTO principles of trade dispute settlement. The article represents the results of the analytical review of the WTO principles reception in the trade dispute settlement in the International Commercial Arbitration Court at the Chamber of Commerce and Industry of the Russian Federation and the London International Arbitration Court. Theoretical and practical value of the study is determined by the need to study the developments in the Regulations of international commercial arbitration jurisdiction of the Russian Federation. The article performs the comparative analysis of the WTO principles reception in the process of trade dispute settlement by the arbitration institutions under study. The WTO principles that are indirectly expressed in theRegulation of ICAC and principles that must be enshrined in the Regulations of ICAC at RCCI are defined. It is concluded that the basic principles of ICAC at RCCI activity should be enshrined in a separate clause of the Regulation of the ICAC.